2008
DOI: 10.1124/mol.107.041814
|View full text |Cite
|
Sign up to set email alerts
|

Salicylate Alters the Expression of Calcium Response Transcription Factor 1 in the Cochlea: Implications for Brain-Derived Neurotrophic Factor Transcriptional Regulation

Abstract: Brain-derived neurotrophic factor (BDNF) is a key neurotrophin whose expression is altered in response to neurological activity, influencing both short-and long-term synaptic changes. The BDNF gene consists of eight upstream exons (I-VII), each of which has a distinct promoter and can be independently spliced to the ninth coding exon (IX). We showed recently that the expression of BDNF exon IV in the cochlea is altered after exposure to salicylate, an ototoxic drug that in high doses is able to induce hearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Long-term administration of salicylate may increase prestin expression and OHC electromotility (Yu et al 2008). CaRF1 is upregulated in these conditions (Singer et al 2008). The authors assume that the dose-dependent effects of salicylate on CaRF1 may result from indirect dose-dependent effects of salicylate on L-type calcium channels in cochlear neurons.…”
Section: Carf Creb and Prestinmentioning
confidence: 97%
See 1 more Smart Citation
“…Long-term administration of salicylate may increase prestin expression and OHC electromotility (Yu et al 2008). CaRF1 is upregulated in these conditions (Singer et al 2008). The authors assume that the dose-dependent effects of salicylate on CaRF1 may result from indirect dose-dependent effects of salicylate on L-type calcium channels in cochlear neurons.…”
Section: Carf Creb and Prestinmentioning
confidence: 97%
“…CaRF cooperates with CREB to mediate the activity-mediated expression of BDNF exon III (Tao et al 2002). An observation that makes CaRF a candidate for regulator of prestin expression is the fact that Carf and prestin are upregulated by salicylate, a substance known for its effect on hearing and tinnitus formation (Singer et al 2008;Yu et al 2008). CREB is a calcium-activated TF which belongs to the basic-leucine zipper family (Kitagawa 2007).…”
Section: Introductionmentioning
confidence: 99%
“…After Cazals’s review, several studies demonstrated the enhanced expression of TRP1 [36], prestin [37] and brain-derived neurotrophic factor (BDNF) [38,39], and morphological changes [40,41]. Prestin is a motor protein involved in the motility of outer hair cells [42].…”
Section: Ototoxicity Induced By Nsaidsmentioning
confidence: 99%
“…Salicylate was shown recently to lead to a change in the opening kinetics of voltage-dependent Ca 2+ channels [106]. These changing Ca 2+ -signaling events cause an up-regulation of BDNF mRNA expression.…”
Section: Discussionmentioning
confidence: 99%